Człowiek w systemie totalitarnym. Życie i dzieło dr. Jerzego Matyjka (1926-2017) - Białkowski , Michał (Fides, Ratio et Patria. Studia Toruńskie, 2017)
Jerzy Matyjek was born on November 14, 1926 in Radziejowice near Żyrardów, in a family with strong patriotic traditions. Since 1942, he was a sworn soldier of Związek Walki Zbrojnej – Armia Krajowa (The Union of Armed Struggle – Home Army). In 1945–1951 he studied medicine at the Faculty of Medicine, Jagiellonian University, and then at the Medical University of Warsaw. His marriage to Barbara Hanna Bodendorf in 1952 started a period of his dynamic activities aiming at popularisation of natural family planning methods. Together with his wife, he visited parishes in the Western Pomerania with lectures and talks explaining the woman’s biological cycle and rising awareness about harmfulness of abortion, very widespread in those days. At that time Jerzy Matyjek worked at the Neurology Ward at the Voivodship Hospital in Koszalin. Due to cumbersome harassment by the Security Service, in 1973 he moved to Toruń and was appointed a head of the Neurology Ward at the Health Care Centre No. 1. In 1974, he became an ordinary member of the Catholic Intelligentsia Club (KIK) in Toruń, and in 1978–1983 he was its president, establishing, for example, the social studies section focusing on studies on the Catholic social sciences. Due to his involvement with the ZNAK (The Sing) movement and close relationships with the Warsaw KIK, the President of the Toruń KIK was investigated under the intelligence operation bearing a code name “Doctor”. The preserved transcripts from talks conducted by the Security Service officers prove his unwavering position and critical perception of the Polish People’s Republic political system. In August 1980 he was a counsellor of the Inter-Enterprise Strike Committee at the Toruń Deck Equipment Production Plant “Towimor”, and in December 1980 he became a member of the Toruń Inter-Enterprise Founding Committee of NSZZ „Solidarność”. He was interned on the day on which the martial law was proclaimed, and initially imprisoned in Potulice. Despite the repeated pressure from the Security Service, he did not signed a declaration of loyalty offering to him a chance of release from the internment. Eventually, he was discharged from the camp in Jaworze on February 23, 1982. After he regained freedom, he was not able to restore activities of the Catholic Intelligentsia Club in Toruń which was disbanded in May 1983. In November 1984, Jerzy Matyjek became a confounder of Committee for commemorating the place of abduction of Priest Jerzy Popiełuszko in Górsk. In the 1980s, he actively supported the Diocese Centre of Assistance for Repressed at the Church of Ascension of the Blessed Virgin Mary in Toruń. After 1989, he was the MP during the first term of the RP Parliament (1991–1993) and was a Counsellor during the second term of the Toruń City Council (1994–1998). In the 1990s, he was involved in development of foundations for the new Toruń Diocese, actively participating in new secular Catholic movements (The Society of Catholics Families of the Toruń Diocese). Jerzy Matyjek died in Toruń after a long illness, on January 31, 2017.